Peran Bahasa Indonesia dalam Proses Rekrutmen dan Seleksi Karyawan di Perusahaan Nasional PT Indomarco Prismatama Cabang Gorontalo - Meilina Widya Dali; Mohamad Aymar; Farel Hasan; Salwa Anita Panto; Prisqila Nera Kaesang; Sintia Sintia; Mutya Zahra Radjulani; Nur Ain Sabidullah; Rahmiyati Inaku; Dita Salsabila Muhsin; Syeril Ana Tasya Harun; Fatmah Zahratusyita Umar; Yunita Putri Rahma Saini; Eko Purwanto Mooduto (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Indonesian as the official language of the country plays a strategic role in the professional environment, especially in corporate human resource management. This study aims to identify the role of the Indonesian language in the employee recruitment and selection process at PT Indomarco Prismatama, a national company with a branch in Gorontalo. The research method used is descriptive with a qualitative approach. Data collection techniques include observation, interviews, and documentation. The results show that Indonesian is not only a medium of communication but also a tool to maintain professionalism, convey company values accurately, and build a positive corporate image. The use of standard Indonesian in job advertisements, interviews, and official correspondence ensures clarity and fairness for all candidates. Therefore, the Indonesian language plays a crucial role in attracting qualified talent and supporting the company's human resource objectives.